2017
DOI: 10.1021/acsphotonics.7b01016
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic Magnetic Purcell Effect

Abstract: Manipulating the spontaneous emission rate of optical emitters with all-dielectric nanoparticles benefits from their low-loss nature and thus provides relatively large extrinsic quantum yield. However, such Purcell effect greatly depends on the orientation of the dipole emitter. Here, we introduce the concept of isotropic magnetic Purcell effect with Purcell factors about 300 and large extrinsic quantum yield (more than 80%) for a magnetic dipole emitter of arbitrary orientation in an asymmetric silicon nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 41 publications
0
34
1
Order By: Relevance
“…More specifically, the resonances of the holey spherical and cylindrical resonators occur at nm and nm with PFs attaining and , respectively. These values of the PF presented here are notably higher than others previously reported when considering for instance cylindrical holes as in 17 ; namely a PF increment of 36 % and 18 % in the spherical and cylindrical resonators, respectively. In both resonators, additionally, a significant part of the emitted power is radiative in nature thus reaching a high quantum efficiency with the values and .…”
Section: Resultscontrasting
confidence: 75%
“…More specifically, the resonances of the holey spherical and cylindrical resonators occur at nm and nm with PFs attaining and , respectively. These values of the PF presented here are notably higher than others previously reported when considering for instance cylindrical holes as in 17 ; namely a PF increment of 36 % and 18 % in the spherical and cylindrical resonators, respectively. In both resonators, additionally, a significant part of the emitted power is radiative in nature thus reaching a high quantum efficiency with the values and .…”
Section: Resultscontrasting
confidence: 75%
“…We demonstrate that coupling to a well-designed optical nanoantenna can increase either the magnetic or electric emission of trivalent europium doped nanoparticles, as predicted theoretically. 31,35,45 Finally, placing the nanoantenna at the extremity of an optical scanning tip provides full control over near-field interactions and the ability to record nanoscale maps of the relative electric and magnetic radiative LDOS (EMLDOS) around resonant nanostructures.…”
mentioning
confidence: 99%
“…16 However, recent progress in nanophotonics has led to the development of nanostructures that enable the utilization of magnetism in optics. 17 By this way, emission enhancement of MD emitters has been studied via split-ring resonators, 18 Diabolo nanoantennas, 19 silicon hollow disks, [20][21][22] silicon nanocavities, 23,24 hyperbolic metamaterials 25 and various dielectric [26][27][28][29][30][31][32][33] and metal nanostructures. 16,[34][35][36] Although, there is a great interest on the enhancement of MD emission by nanophotonic structures, most of the research has been focused on the visible spectrum and few studies have been reported up to present for the near-infrared (NIR) range.…”
Section: Introductionmentioning
confidence: 99%